Etika Kristen Dalam Roma 12:1–21: Landasan Pastoral Untuk Mengatasi Budaya Ostentasi - Eko Raharjo Raharjo; Jefit Sumampouw; Jonar Situmorang (Jurnal Apokalupsis, 2025)
The rapid development of digital technology, particularly social media, has fostered a culture of ostentation that encourages individuals to construct and display self-image in pursuit of social recognition. This phenomenon not only affects psychological and social dimensions but also raises significant ethical and spiritual concerns within Christian life. This study aims to examine the culture of ostentation from the perspective of Christian ethics based on Romans 12:1–21 and to formulate it as a pastoral framework for addressing the challenges of the digital age. The research employs a qualitative method using a literature review and exegetical analysis of the biblical text, supported by relevant studies in biblical theology and contemporary Christian ethics. The findings reveal that Paul’s ethical teaching in Romans 12:1–21 is holistic and transformative, beginning with the renewal of the mind as the foundation for reorienting the believer’s life. Humility is emphasized as the primary antithesis to ostentatious behavior, while sincere love serves to correct performative expressions commonly found in social media practices. Furthermore, the principles of living in peace and overcoming evil with good present a countercultural ethical alternative to the competitive and image-driven nature of digital culture. The pastoral implications underscore the church’s strategic role in cultivating authentic digital spirituality through spiritual formation, contextual teaching, and the nurturing of faith communities. Thus, this study contributes to the development of Christian digital ethics by positioning Romans 12:1–21 as a relevant and practical theological foundation for shaping Christian character in the digital era.